Molecular imaging within the lower gastrointestinal tract: From feasibility to future - Rath, Timo; Kiesslich, Ralf; Neurath, Markus; Atreya, Raja (Digestive Endoscopy, 2018)
Molecular imaging is based on the labelling of defined molecular targets through the utilization of fluorescently linked probes and their subsequent detection with high-resolution endoscopic devices, thereby enabling visualization of single molecules including receptors. Whereas early studies have used molecular imaging for improved visualization and detection of early dysplasia and cancer as well as for assessing intestinal inflammation and inflammation-associated cancer within the gastrointestinal (GI) tract, more recent studies have impressively demonstrated that molecular imaging can also be used to characterize and visualize the molecular fingerprint of cancer and inflammation in vivo and in real time. With this, molecular imaging can be used to guide expression-tailored individualized therapy. With the rapid expansion and diversification of the repertoire of biological agents utilized in inflammatory bowel disease and cancer, this approach is gaining increasing attention. Within this review, we first summarize the technical components commonly used for molecular imaging and then review preclinical and clinical studies and evolving clinical applications on molecular imaging within the lower GI tract. Molecular imaging has the potential to significantly change endoscopic diagnosis and subsequent targeted therapy of gastrointestinal cancer and chronic gastrointestinal diseases.
EVALuna2:35133